Graphic design analysis of Studio Ghibli animation film poster "From Up On Poppy Hill" - Ismoyo, Katrin Nur Nafi'ah (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2024)
Graphic design, one of the fields of science in the world of fine arts, is currently trendy among the general public. Today, graphic design has many fields of science, from photography to film. One of the entertainment segments of graphic design currently widely available to the general public is animation, which is part of the film industry. The film itself has the meaning of an image presented on a big screen and has audio-visual elements. This study uses qualitative research methods to analyse the poster work of the animated film "From Up On Poppy Hill" by Studio Ghibli. The findings are not obtained through statistical procedures or calculations in qualitative research, so the research is descriptive. The results of the study using graphic design analysis on the poster of the animated film Studio Ghibli entitled "From Up On Poppy Hill" are that the film poster does not have many threats to compete with posters of other films because Studio Ghibli already has its market in the animated film industry. Many fans highly anticipate its films with character. In addition, the graphic design elements on the poster are designed and calculated carefully to meet the rules of beauty and optimal message delivery.